1999
DOI: 10.1007/s00585-999-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of equatorial Kelvin waves at eastern ocean boundaries Part II: Pacific and Atlantic Oceans

Abstract: Abstract. The effect of viscosity, non linearities, incident wave period and realistic eastern coastline geometry on energy fluxes are investigated using a shallow water model with a spatial resolution of 1/4 degree in both meridional and zonal directions. Equatorial and mid-latitude responses are considered. It is found that (1) the influence of the coastline geometry and the incident wave period is more important for the westward energy flux than for the poleward flux, and (2) the effect of the inclination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The R k < 1 values in the CP and >1 values in the EP are also noticeable. Mechanisms controlling sea level variabilities of the central-eastern Pacific are different from those of the WTP (e.g., Bigg & Gill, 1986;Boutle et al, 2007;Qiu & Lukas, 1996;Soares et al, 1999), and therefore the asymmetric SLA responses there are out of the scope of the present study.…”
Section: S2mentioning
confidence: 95%
“…The R k < 1 values in the CP and >1 values in the EP are also noticeable. Mechanisms controlling sea level variabilities of the central-eastern Pacific are different from those of the WTP (e.g., Bigg & Gill, 1986;Boutle et al, 2007;Qiu & Lukas, 1996;Soares et al, 1999), and therefore the asymmetric SLA responses there are out of the scope of the present study.…”
Section: S2mentioning
confidence: 95%
“…A similar decay is found in the linear model where it is due to viscous processes. Using a shallow water model, Soares et al (1999) found that a realistic shape of the coastline was more important than nonlinear effects for an accurate representation of the poleward energy flux at intraseasonal frequencies. In our fully three dimensional model (Fig.…”
Section: Horizontal Structure Of the Intraseasonal Signalmentioning
confidence: 99%
“…Note that the eastern boundary will also contribute a delay term to the DAO, however equatorial Kelvin wave reflection from eastern boundaries is weak as the bulk of the wave propagates along the coast [16]. For this reason we may ignore these effects.…”
Section: B Dao Wave Propagationmentioning
confidence: 99%
“…FIG.11: Numerical solutions to the coupled DAO(16), with α1 = 0.5 in region 1, α2 = 0.75 in region 2, δ = 4 in both regions and γ = 0.1.…”
mentioning
confidence: 99%